Avaliação da qualidade de vida do paciente renal crônico submetido à hemodiálise e sua adesão ao tratamento farmacológico de uso diário - Terra, Fábio de Souza (2007)
This study evaluated the QL of end-stage renal patients submitted to hemodialysis and their adhesion to daily pharmacologic treatment knowing their life expectancy and the main complications presented during HD It is an epidemiologic descriptive tranversal and quantitative research carried out at a hemodialysis clinic of a university hospital of Alfenas State of Minas Gerais Brazil with the participation of all the 30 dialysis patients in the period of the collection of data A questionnaire was used for the obtainment of data about the participants' characterization adhesion to pharmacologic treatment and life expectation QL was analyzed through the instrument WHOQOL-bref of the World Health Organization The data were tabulated in the statistical program SPSS version 10.0 and analyzed by means of the medium score with application of the following tests Qui-square Coefficient of Correlation of Pearson Test of Wilcoxon Student s t test Cronbach s Alpha Coefficient The results showed that most of the interviewees referred that HD interfered in their professional activities and in leisure and recreation but 53.33% were calm during the permanence in the clinic The most frequent complications were the arterial hypotension vomit and dizziness All the patients take medicines mainly antihypertensives With regard to knowledge of the indication of the medicines 40% of the dialysis patients know all the drugs that they take Thirty patients informed to take the medicines daily but 16.66% have already interrupted the treatment on their own account due to adverse reactions The average scores of QL were General QL 3.26 physical domain 3.10 psychological domain 3.58 social relationships 4.19 and environment 3.54 Therefore the participants of the study classified their QL as being above "neither bad, nor good" while the domain social relationships was evaluated between "good" and "very good" The variables did not interfere in the patients' QL in other words they did not present any correlation with the domains of WHOQOL-bref Through the reproducibility it was verified that the interviewees' QL was stable between the "test" and the "retest" having satisfactory reliability while the internal consistency of WHOQOL-bref was acceptable for the facets and domains indicating a homogeneity in the appraised items The main expectation of the patients' life is receiving a renal transplantation 82.35% are in the waiting list and 47.06% encountered the refusal of their relatives in donating the organ It can be verified that the instrument WHOQOL-bref showed to be effective to evaluate QL of end-stage renal patients submitted to HD thus being a reliable instrument for such a measure Finally dialysis patients will have a better QL when they are informed about their disease and treatment when cared for in a solid supportive system and rehabilitation in order to make them capable to lead an active productive and self-sufficient life